2014
DOI: 10.1080/09670262.2014.984347
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of rhodolith formation in the Corallinales (Rhodophyta)

Abstract: Although the ecological importance of rhodolith (maerl, free-living coralline algae) beds is well-known, rhodolith-forming species have been neglected in molecular phylogenetic studies. This is the first molecular systematic study aimed at understanding whether the rhodolith habit is a fixed feature in lineages and determining the relationship (phylogenetic vs. environmental) between rhodolith and crustose habits. Phylogenetic relationships of rhodolith-forming species and encrusting coralline algae at generic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 48 publications
3
32
0
Order By: Relevance
“…Results of the psbA analysis (Fig. 1) are similar to the results of the psbA analysis presented by Hernández-Kantún et al (2015, fig. 2) with regards to the relationship between Lithothamnion spp., Phymatolithon calcareum (Pallas) W.H.Adey & McKibbin, and Hapalidiaceae sp.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Results of the psbA analysis (Fig. 1) are similar to the results of the psbA analysis presented by Hernández-Kantún et al (2015, fig. 2) with regards to the relationship between Lithothamnion spp., Phymatolithon calcareum (Pallas) W.H.Adey & McKibbin, and Hapalidiaceae sp.…”
Section: Discussionsupporting
confidence: 78%
“…I and J and specimen GAL15736 is intriguing considering Hernández-Kantún et al (2015) showed that GAL15736 possessed "flared" epithallial cells. This lineage received strong support in the single-gene analyses of psbA (PP=1, BS=100%) and COI (PP=1, BS=90%) and in the multi-gene phylogeny (BS=100%).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, psb A and rbc L sequences of these species (Hernandez‐Kantun et al. ) and cox 2,3 sequences of Lithophyllum sp. (Hernandez‐Kantun et al.…”
Section: Methodsmentioning
confidence: 99%
“…, , Hernandez‐Kantun et al. ,b; Atlantic Iberian Peninsula, Pardo et al. ; Warm Temperate to Tropical Western Atlantic Ocean, Mateo‐Cid et al.…”
mentioning
confidence: 99%
“…, Hernandez‐Kantun et al. ). Herein, we sequenced type material to begin resolving the genus Lithophyllum Phillipi, based on its generitype, L. incrustans Philippi (type locality: Sicily) and related species in Europe.…”
mentioning
confidence: 99%